The role of corporate governance in achieving clean audit in Johannesburg Market entity - Nephawe, Azwianewi Cedric (My University, 2024)
The focus of this study pertains to the Johannesburg Market entity, which has consistently obtained an unqualified audit opinion for duration of four consecutive years. Using a quantitative approach, the research was driven by the conviction that good governance is indispensable for the promotion of transparent and ethical administration. The objective of this study was to investigate the role of corporate governance in achieving clean audits in the Johannesburg Market entity. The presence of minimal audit findings is regarded as a reliable indicator of effective and reliable governmental administration. The study used a quantitative study approach, a simple random sampling technique and an online questionnaire to collect data. Sixty-one respondents comprised of 40 males and 21 females participated in this study. The study demonstrated a significant association between effective corporate governance and an unblemished audit. The aforementioned observation highlights the detrimental impact of either mismanagement or embezzlement of public funds on the delivery of vital services, thereby underscoring the significance of good governance in ensuring transparent administration. The research emphasised the consistent implementation of effective governance practices to safeguard the overall welfare of the organisation. The role of governance in maximising the efficiency of resource allocation through auditing, especially internal auditing, serves an essential purpose in fostering accountability, transparency, openness and participation. The research is in accordance with the notion that a well governed society is characterised by effectively managed public resources and efficient provision of services. Moreover, the research underscored the discourse prevalent in the public entity of South Africa regarding the attainment of clean audit outcomes and the enhancement of governance mechanisms. In this study, a descriptive data analysis approach was applied. Quantitative in nature and approach, data collected through the use of an online questionnaire were used as the source of data analysis. A questionnaire was emailed to respondents (ANNEXURE C: QUESTIONNAIRE OF THE STUDY on page 144.). The response was categorised in accordance with the descriptive tables.The data were subjected to analysis using the Statistical Package for the Social Sciences (SPSS) Version 25.0. The findings concluded that the entity's management adopts a strategic approach to enhance corporate governance and control systems, thereby establishing efficient governance and control mechanisms within the entity.
Thesis (MBA.) -- University of Limpopo, 2023
Keywords: Corporate governance; Clean Audit; Risk management; Audit committee; Corporate governance; Audit trails; Public administration -- Moral and ethical aspects; Risk management